Impact of Firm-specific Factors on the Financial Performance of Nepalese Microfinance Institutions - Shrestha, Purna Man (Journal of Business and Management, 2023)
Background: Microfinance institutions (MFIs) are established with the aim of providing an opportunity to financially deprived people to make them financially independent and come out of poverty. To provide financial assistance to the targeted people, MFI must be able to improve their financial performance. Thus, the financial manager of MFI needs to identify the major factors that influence their financial performance. Objectives: This paper aims to analyze the impact of firm-specific factors on the financial performance of Nepalese Microfinance Institutions (MFIs. Methods: This paper has applied descriptive and causal comparative research design. The annual panel data of 29 microfinance companies listed in the Nepal stock exchange for the period of 2010/11 to 2020/21 has been used. To identify the impact of firm-specific factors on the financial performance of Nepalese MFIs, an appropriate multivariate regression model is selected based on the result of the Breusch and Pagan Lagrangian multiplier test and the Hausman test. Results: Using the fixed effect regression model, this paper found the significant influence of firm-specific factors on the financial performance of Nepalese MFIs. Further, this study found a significant positive impact on deposit ratio, management efficiency, and weighted average interest rate spread and a significant negative impact of asset quality on the financial performance of Nepalese MFIs. Conclusion: This paper concluded that the financial performance of Nepalese MFIs could can be improved by increasing the deposit ratio, management efficiency, and weighted average interest rate spread. On the other hand, the study also concluded that Nepalese MFIs should maintain a lower level of non-performing loans to achieve a higher level of financial performance.